Between resistance and demobilization. A quantitative approach to the study of the workers conflict in Argentina, 2006 – 2022 - Piva, Adrián (2025)
The objective of this article is to develop a quantitative analysis of the worker's conflict in Argentina between 2006 and 2022 with special emphasis on the period opened in 2012. The analysis seeks to explain the trends and breaks in its evolution by integrating the economic, institutional, and political perspectives of the study of the conflict as moments of an analysis of power relations. This allows us to transcend the identification of correlations between variables to, based on the relationships found, insert the various dimensions of the process into a historical narrative.